Bank-Line Behaviour of the Main Rivers Located Within Sundarbans Using Digital Shoreline Analysis System - Anam, Md Manjurul; Jabir, Abdullah Al; Hasan, GM Jahid (MIST International Journal of Science and Technology, 2021)
Sundarbans, the largest mangrove forest located over the GBM basin, has impacted lives of millions over the years. Standing against various natural disasters, rivers of Sundarbans have undergone major issues such as erosionaccretion of both the banks. The paper deals with a combination of remote sensing and Digital Shoreline Analysis System (DSAS), studying temporal behaviour of bank-lines along the main rivers of Sundarbans for the last three decades. The course of main rivers spanning from southwest Baleswar to west Bengal Bidyadhari within coverage of 10,000 sq. km. has been analyzed in this study. DSAS, the extension tool of ArcGIS, was used for monitoring the rate-ofchange from multiple historic bank-line positions extracted from satellite images. Comparison of historic bank-lines between different rivers of Sundarbans was done based on Net Bank-line Movement (NBM) with an interval of five years. Finally, the results were presented graphically to get a better understanding of the bank-line behaviour. The study revealed that the western region of mangrove prevails eroding behaviour than the eastern region. Increased rates of riverward movement due to accretion was found from 2008-2013. These results are important for future monitoring and proper management within the coastal communities surrounding the mangrove forest. MIJST, Vol. 9(1), June 2020: 11-21